OVERLAPPING TERRITORIES: THE PROXIMITY OF STRANGERS - Voragen, Roy (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2009)
In the era of globalization we in a world of overlapping territoriesand strangers are now always proximate, her or his otherness canno longer be denied. Present-day modernity is characterized byuncertainty; reason and knowledge-based science are questioned.There is a need for a revaluation of culture, civilization, individualand group identity. This also calls for a moral reassessment ofsociety and the nation-state.